The influence of intentions on leaders of firms’ engagement in CSR behaviors - Cruz, C. L. (International Forum on Management, 2022)
Purpose-driven leadership brings inspiration to stakeholders, creates future goodwill, and provides differentiation versus competition. Nonetheless, more than words, what really matters are the actions that materialize that purpose. The objective of this study is to explore the key influences on behaviors’ intentions of Portuguese firm’s leaders to put CSR strategies into action, applying the theory of planned behavior. Thematic analysis is the qualitative method used in this research, involving reading transcripts from 19 semi-structured interviews to leaders that helped to identify patterns and meaning across the data. The outcome of this work is a contribution to understand the importance of individuals implementing CSR initiatives, revealing how leaders can influence CSR decisions, with concrete actions, valued by stakeholders as part of the vison and strategy of managing with purpose.